Investigating spatial macroscopic metastability of perovskite solar cells with voltage dependent photoluminescence imaging. (1st April 2023) - Koutsourakis, George; Worsley, Carys; Spence, Michael; Blakesley, James C; Watson, Trystan M; Carnie, Matt; Castro, Fernando A
Abstract: Metastability is a characteristic feature of perovskite solar cell (PSC) devices that affects power rating measurements and general electrical behaviour. In this work the metastability of different types of PSC devices is investigated through current–voltage ( I – V ) testing and voltage dependent photoluminescence (PL-V) imaging. We show that advanced I – V parameter acquisition methods need to be applied for accurate PSC performance evaluation, and that misleading results can be obtained when using simple fast I – V curves, which can lead to incorrect estimation of cell efficiency. The method, as applied in this work, can also distinguish between metastability and degradation, which is a crucial step towards reporting stabilised efficiencies of PSC devices. PL-V is then used to investigate temporal and spatial PL response at different voltage steps. In addition to the impact on current response, metastability effects are clearly observed in the spatial PL response of different types of PSCs. The results imply that a high density of local defects and non-uniformities leads to increased lateral metastability visible in PL-V measurements, which is directly linked to electrical metastability. This work indicates that existing quantitative PL imaging methods and point-based PL measurements of PSC devices may need to be revisited, as assumptions such as the absence of lateral currents or uniform voltage bias across a cell area may not be valid.